2019
DOI: 10.1038/s41598-019-52856-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of microRNA in follicular fluid in women with and without PCOS

Abstract: Several studies have shown the expression of small non-coding microRNA (miRNA) changes in PCOS and their expression in follicular fluid has been described, though the number of studies remains small. In this prospective cohort study, miRNA were measured using quantitative polymerase chain reaction (qPCR) in 29 weight and aged matched anovulatory women with PCOS and 30 women without from follicular fluid taken at the time of oocyte retrieval who were undergoing in vitro fertilization (IVF); miRNA levels were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 38 publications
2
41
2
Order By: Relevance
“…Further, it is of interest that let-7b-3p correlated with AMH in PCOS women, as AMH has been suggested as a biomarker of PCOS though of low sensitivity ( 31 , 32 ). When weight matched obese PCOS and control women are compared, the number of miRNA that differ between groups are much fewer than those previously reported in the literature ( 33 ), and none of the miRNA reported for that obese cohort differed in this study. As expected, several of the miRNA found in the obese study previously reported were associated with insulin resistance ( 34 ) whilst the four miRNA described here were not.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Further, it is of interest that let-7b-3p correlated with AMH in PCOS women, as AMH has been suggested as a biomarker of PCOS though of low sensitivity ( 31 , 32 ). When weight matched obese PCOS and control women are compared, the number of miRNA that differ between groups are much fewer than those previously reported in the literature ( 33 ), and none of the miRNA reported for that obese cohort differed in this study. As expected, several of the miRNA found in the obese study previously reported were associated with insulin resistance ( 34 ) whilst the four miRNA described here were not.…”
Section: Discussioncontrasting
confidence: 67%
“…In this study, analysis of the combined PCOS and control women revealed that miR-1260a correlated with FAI and AMH, but this correlation was not found in obesity with insulin resistance (33). It is reported that miR-1260a is associated with type 2 diabetes (35) as is miR-424 (36), whilst miR-let 7 has been associated with a reduction in insulin signaling (36).…”
Section: Discussionmentioning
confidence: 59%
“…MiRNAs are non-coding RNAs of approximately 22 nucleotides in length that post-transcriptionally regulate gene expression; miRNAs are differentially found in PCOS compared with normal controls. 156 , 157 Their binding to target messenger RNA (mRNA) causes mRNA cleavage, translational repression and mRNA decay. 158 161 miRNAs are released by many tissues, including adipose tissues, and act as both endocrine and paracrine messenger between various target organs.…”
Section: Future Treatment Optionsmentioning
confidence: 99%
“…By using the littermate model, Mohamed et al verified that TXNIP deletion ameliorated the inflammatory response in high fat diet-induced nonalcoholic steatohepatitis via deactivation of the TLR2-NLRP3 inflammasome axis [ 41 ]. Furthermore, miR-382-5p was shown to be negatively correlated with a free androgen index [ 42 ]. The PCOS group had a significantly higher free androgen index than controls [ 43 ].…”
Section: Discussionmentioning
confidence: 99%